Destrezas Lectoras - Sigcha Suatunce, Nancy Veronica (2016)
The following research work is framed in the importance of teaching and learning language and literature, as a fundamental tool for social interaction; liaises with the theme of reading skills and meaningful learning for better emotional form of communication. Teachers and the educational community face a serious conflict regarding reading skills; this is due to poor development of skills in reading, current information is based on analyzing the influence of the application of methodological guide that allows compliance the aim of improving communication through education, relationships among students and parents. That is, to achieve change the old way of teaching aside the traditional method; School of Basic Education “Federación Deportiva de Cotopaxi” there is no reading habits, reading areas, where the student form his own judgment making the student is capable of forming part of learning. Among one of the goals is to develop critical, reflective, actively involved citizens, to interact as an effective environment that enables the learner to develop the skills of communication. The research is taken into account as a reference to 1040 beneficiaries through a diagnosis to students, parents and teachers, it has been possible to demonstrate the poor lack of reading by students which affect the teaching process learning, resulting in poor academic performance. This is necessary for teacher training in the area of language and literature according to reality by a methodological guide and socialization workshops encouraging student interest in reading and improves their reasoning.